2019
DOI: 10.1021/acsami.9b14971
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Heating of Silicon Carbide Fibers under Radio Frequency Fields and Application in Curing Preceramic Polymer Composites

Abstract: Silicon carbide (SiC) fibers are widely used as a reinforcement in ceramic matrix composites due to their high mechanical strength and superior thermal resistance. Here, we investigate the rapid radio frequency (RF) heating response of two types of SiC fibers (Hi-Nicalon and Sylramic) in the 1–200 MHz frequency range. Hi-Nicalon fibers exhibit a surprisingly rapid RF heating response of 240 °C/s in the perpendicular orientation, and this property could be exploited for oven-free and noncontact processing of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 44 publications
1
21
0
1
Order By: Relevance
“…Our previous work has shown rapid RF heating property of commercial Hi‐Nicalon silicon carbide fibers due to presence of turbostratic carbon on surface; these fibers show rapid RF heating when aligned parallel to the electric field. [ 26 ] A 1 nm platinum sputter coating was applied to the surface of these fibers using a sputter coater. Figure A shows the SEM images of SiC fibers used as susceptors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work has shown rapid RF heating property of commercial Hi‐Nicalon silicon carbide fibers due to presence of turbostratic carbon on surface; these fibers show rapid RF heating when aligned parallel to the electric field. [ 26 ] A 1 nm platinum sputter coating was applied to the surface of these fibers using a sputter coater. Figure A shows the SEM images of SiC fibers used as susceptors.…”
Section: Resultsmentioning
confidence: 99%
“…[ 23 ] In our recent work, carbon nanotubes and silicon carbide fibers were used as RF susceptors to cure preceramic polymers to silicon carbides for noncontact processing in 3D printing, composite manufacturing, and fiber processing. [ 18 ] Our group has studied RF susceptive nanomaterials including multi walled carbon nanotube (MWCNT), [ 20 ] metallic and semiconducting single walled carbon nanotube, [ 24 ] MXenes, [ 25 ] and silicon carbide fibers; [ 26 ] and these materials heat up to significantly high temperatures under low‐power RF radiation. The presence of sp 2 carbon in MWCNT and surface of SiC fibers results in rapid RF heating response.…”
Section: Introductionmentioning
confidence: 99%
“…4). 25,[35][36][37] RF elds have successfully shown composite processing capabilities such as curing of carbon ber (CF) reinforced thermosetting composites and out-of-oven ceramic manufacturing using multiple susceptors. Thermosetting prepregs are fabricated continuously by using energy-expensive methods such as large convection ovens, or infra-red lamps.…”
Section: Volumetric Heatingmentioning
confidence: 99%
“…4 Volumetric RF heating has successfully shown application in (counterclockwise, from top-right) ceramics and carbon fiber composite fabrication, catalytic reactors, thermally driven chemical reactions, and medical applications. 25,[35][36][37] Nanoscale Adv. CNT circuits ten times faster than conventional methods, identifying faulty circuits more reliably.…”
Section: Minireview Nanoscale Advancesmentioning
confidence: 99%
“…Our group has previously demonstrated that certain nanomaterials act as RF susceptors, such that they will heat rapidly in response to an applied field; this allows for volumetric heating in a composite with susceptor fillers, such as carbon nanotubes (CNTs), laserinduced graphene (LIG), MXenes, [24] and carbon black. [23,[25][26][27] This phenomenon has been applied to a range of manufacturing applications such as welding of polymer sheets, [28] curing of epoxy nanocomposites [23] or preceramic polymer composites, [29] and screening of CNT circuits. [25,27] We have shown that the sample does not have to be directly connected to the power source, and it can heat the carbon nanomaterials at different applicator configurations (parallel plate and fringing field).…”
mentioning
confidence: 99%